Pengaruh Kepemilikan Institusional, Capital Intensity, Inventory Intensity, Dan Profitabilitas Terhadap Tax Avoidance - Lamesya Fazilah; Afridian Wirahadi Ahmad; Dita Maretha Rissi (CV. ALIM'SPUBLISHING, 2024)
This study aims to analyze the effect of institutional ownership, capital intensity, inventory intensity, and profitability on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. This research is quantitative study. The population of this study consists of all manufacturing companies listed on the IDX during the period 2019-2023. The sampling technique used is purposive sampling. Based on the established criteria, there are 47 companies that meet the criteria, resulting in 235 data points that constitute the sample in this study. The data source is obtained from the BEI website and the related company website. Data was processed using SPSS version 29 and analyzed using a multiple regression model to test the influence of each variable on tax avoidance. The research results show that simultaneously, institutional ownership, capital intensity, inventory intensity, and profitability affect tax avoidance. Partially, institutional ownership, capital intensity, and inventory intensity have a positive effect on tax avoidance, while profitability does not affect tax avoidance